Preoperative diagnosis of primary ovarian lymphoma: a case report and a decade of insights - Liu, Wei; Xu, Houyun; Hu, Jibo; Yu, Xiping; Zhou, Junjie; Hu, Hongjie (Frontiers in Oncology, 2024)
Through a comprehensive retrospective analysis of a 52-year-old woman with primary ovarian lymphoma (POL) and a review of similar cases over the past decade in the PubMed database, we gained several key insights into improving the understanding of POL among clinicians and radiologists for accurate diagnosis. POL is more prevalent among women in their 40s and usually presents with clinical manifestations of a solid mass (typically over 10 cm) and abdominal pain with B symptoms. Four imaging features show promise as indicators of potential diagnostic value in POL: the ovarian retention sign, touching ovaries, vascular floatation, and the sandwich sign. More than half of primary ovarian diffuse large B-cell lymphoma (DLBCL) cases have elevated lactate dehydrogenase (LDH) or carbohydrate antigen 125 (CA-125) levels. This comprehensive understanding of POL suggests that the combination of these four imaging features with elevated levels of CA-125 and LDH might help in the diagnosis of POL preoperatively, preventing unnecessary surgical interventions.